2007
DOI: 10.1083/jcb.200608122
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal inhibition between Pax7 and muscle regulatory factors modulates myogenic cell fate determination

Abstract: Postnatal growth and regeneration of skeletal muscle requires a population of resident myogenic precursors named satellite cells. The transcription factor Pax7 is critical for satellite cell biogenesis and survival and has been also implicated in satellite cell self-renewal; however, the underlying molecular mechanisms remain unclear. Previously, we showed that Pax7 overexpression in adult primary myoblasts down-regulates MyoD and prevents myogenin induction, inhibiting myogenesis. We show that Pax7 prevents m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
276
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(311 citation statements)
references
References 38 publications
(90 reference statements)
24
276
0
11
Order By: Relevance
“…Rage -/-myoblasts have higher levels of Pax7, greater proliferation potential and lower differentiation potential than WT myoblasts, and deleting Rage promotes asymmetric division of myoblasts 42 . MyoD and MyoG downregulate Pax7 post-translationally 43 ; however, in myoblasts committed to differentiation, post-transcriptional downregulation is mediated by miR-1, miR-206 and miR-486 (refs 30,44). Here we showed that miR-431 regulates SC functions in miR-431 TG mice and we provide convincing evidence that the Pax7 level is tightly controlled by miR-431 in SCs in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Rage -/-myoblasts have higher levels of Pax7, greater proliferation potential and lower differentiation potential than WT myoblasts, and deleting Rage promotes asymmetric division of myoblasts 42 . MyoD and MyoG downregulate Pax7 post-translationally 43 ; however, in myoblasts committed to differentiation, post-transcriptional downregulation is mediated by miR-1, miR-206 and miR-486 (refs 30,44). Here we showed that miR-431 regulates SC functions in miR-431 TG mice and we provide convincing evidence that the Pax7 level is tightly controlled by miR-431 in SCs in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by inducing the expression of Id2 and Id3, Pax7 may act to block the premature differentiation of quiescent satellite cells. In addition, Pax7 may also block skeletal muscle differentiation by targeting myogenic bHLH proteins for degradation (Olguin et al, 2007). In contrast, in activated satellite cells, Pax7 may act to directly induce the expression of Myf5 (Bajard et al, 2006) and MyoD (Hu et al, 2008), which in turn will compete with Id proteins for E protein dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…There are four main MRFs that control normal myogenesis: Myf5, MyoD, MRF4, and myogenin. The paired box transcription factor Pax7 is a key protein that coordinates the transcription of the MRFs and progression of SCs through the developmental pathway known as the myogenic program (8,16,39,43,44). SCs have been implicated as a significant factor contributing to the inability of aged muscle to repair/ remodel.…”
mentioning
confidence: 99%